Refrigerant alternative and optimization under the constraint of the greenhouse gas emissions reduction target - Wang, Huihui; Zhao, Linjia; Cao, Ruoxin; Zeng, Weihua (Journal of cleaner production, 2021)
Fluorinated gases are considered greenhouse gases and have a global warming effect up to 22,800 times greater than that of carbon dioxide. Fluorinated gases are widely used as room air conditioner refrigerants. In view of the current lack of well-equipped refrigerant replacement technology and research on comprehensive and systematic refrigerant alternative schemes, we propose a decision-making method system for optimizing room air conditioner refrigerant alternative schemes suitable for meeting future greenhouse gases emissions reduction target constraints by integrating the life cycle assessment method, the system dynamics method and the multi-objective programming method. In accordance with the requirements of the Montreal Protocol and other relevant fluorine-containing substance elimination plans, four scenarios for refrigerant alternative schemes were designed, which include Business as usual scenario, Convention Scenario, Design Scenario and Ideal Scenario, respectively. The Convention Scenario is based on the refrigerant phase-out plan stipulated by international conventions in China; the Ideal Scenario is based on the use of refrigerants with minimal environmental impact within the range of available predictable technologies; and the Design Scenario is designed according to the degree of strictness between the Convention Scenario and the Ideal Scenario and used to propose more reasonable and feasible refrigerant use planning schemes. The results show that the ozone depletion ability of refrigerants will be eliminated with the phase-out of hydrochlorofluorocarbon refrigerant HCFC-22. The total cost of refrigerant substitution work under different alternative scenarios will cost a total of $1.378 billion to $1.672 billion, which is worthwhile considering the considerable environmental benefits. The refrigerant dosage scheme under design scenario II, which is 50% faster than the conventional phase-out scheme, is the optimal scheme for future refrigerant replacement phase-out in the room air conditioner industry. Under this scenario, the total economic cost is $1.672 billion; additionally, compared with those under the business as usual scenario, the greenhouse effect intensity will decrease by 78.2%, the safety risk will decrease by 6.8%, the energy consumption will decrease by 60.4% and the ozone depletion ability will decrease by 99.8%. •We proposed a decision-making method system for optimizing room air conditioner refrigerant alternative schemes.•The economic cost of refrigerant replacement work is positively correlated with environmental benefits.•The refrigerant consumption planning roadmap for the future room air conditioner industry was obtained.•HC-290 is an important future alternative refrigerant that has better comprehensive performance than HCFC-22 and HFC-410A.